You are Here: Home >< Maths

# Solving equations with e - C3 Watch

Announcements
1. e^2x + e^x = 6

I made e^x = y and e^2x = y^2
then i factorised to get y=-3 and y=2
replace y with e^x
NOTE: i used y instead if x because it makes the next part easier to understand.

Then i have e^x = -3 and e^x = 2
Is this wrong because when you add an ln in front to get x you end up with x = ln-3 and x = ln2
2. (Original post by kiiten)
e^2x + e^x = 6

I made e^x = y and e^2x = y^2
then i factorised to get y=-3 and y=2
replace y with e^x
NOTE: i used y instead if x because it makes the next part easier to understand.

Then i have e^x = -3 and e^x = 2
Is this wrong because when you add an ln in front to get x you end up with x = ln-3 and x = ln2
It is right, but you discard the negative solution as being invalid

Posted from TSR Mobile
3. (Original post by kiiten)
e^2x + e^x = 6

I made e^x = y and e^2x = y^2
then i factorised to get y=-3 and y=2
replace y with e^x
NOTE: i used y instead if x because it makes the next part easier to understand.

Then i have e^x = -3 and e^x = 2
Is this wrong because when you add an ln in front to get x you end up with x = ln-3 and x = ln2
No, just reject x=ln(-3) as you can't take the natural log of a number less than or equal to 0.
4. (Original post by kingaaran)
It is right, but you discard the negative solution as being invalid

Posted from TSR Mobile
(Original post by NotNotBatman)
No, just reject x=ln(-3) as you can't take the natural log of a number less than or equal to 0.
Ahh i see, so i was right. Does that mean that x = ln2 or am i supposed to write it in a different form?
5. (Original post by kiiten)
Ahh i see, so i was right. Does that mean that x = ln2 or am i supposed to write it in a different form?
Yes, normally you would leave it in exact form unless told otherwise.
6. (Original post by NotNotBatman)
Yes, normally you would leave it in exact form unless told otherwise.
Right and would a similar approach work for

e^4x - e^2x = 6 making e^4x = x^2 and e^2x = x ?
7. (Original post by kiiten)
Right and would a similar approach work for

e^4x - e^2x = 6 making e^4x = x^2 and e^2x = x ?
yes.
8. (Original post by NotNotBatman)
yes.
Thanks
9. (Original post by kiiten)
Right and would a similar approach work for

e^4x - e^2x = 6 making e^4x = x^2 and e^2x = x ?
However, instead of making that substitution, you could note that:

e^4x - e^2x - 6 = 0

(e^2x - 3 ) (e^2x + 2) = 0

Hence, e^2x = 3 or e^2x = -2 (the latter which doesn't have a solution!).

TSR Support Team

We have a brilliant team of more than 60 Support Team members looking after discussions on The Student Room, helping to make it a fun, safe and useful place to hang out.

This forum is supported by:
Updated: October 2, 2016
Today on TSR

### Oxbridge

Even more elitist than everyone thought?

### Physically ill after being cheated on

Discussions on TSR

• Latest
• ## See more of what you like on The Student Room

You can personalise what you see on TSR. Tell us a little about yourself to get started.

• Poll
Useful resources

### Maths Forum posting guidelines

Not sure where to post? Read the updated guidelines here

### How to use LaTex

Writing equations the easy way

### Study habits of A* students

Top tips from students who have already aced their exams

## Groups associated with this forum:

View associated groups
Discussions on TSR

• Latest
• ## See more of what you like on The Student Room

You can personalise what you see on TSR. Tell us a little about yourself to get started.

• The Student Room, Get Revising and Marked by Teachers are trading names of The Student Room Group Ltd.

Register Number: 04666380 (England and Wales), VAT No. 806 8067 22 Registered Office: International House, Queens Road, Brighton, BN1 3XE

Reputation gems: You get these gems as you gain rep from other members for making good contributions and giving helpful advice.